Modal analysis of annular optical waveguides bounded by non-coaxial dielectric cylindrical boundaries by Goell's point matching method - Singh U.K.; Khastgir P.; Singh O.N. (My University, 2025)
This paper reports the modal behaviour of an optical waveguide of annular cross-section in which the guiding region lies between two non-concentric circular boundaries. Although the authors treated this problem by a semi-analytical method earlier, in this communication for obtaining the details of modal behaviour, Goell's point matching method is used. A brief study of the near cutoff situation is also presented. Numerical computations show that this waveguide can support fewer modes than a standard annular waveguide of concentric circular cross-section.